2021
DOI: 10.1186/s13046-021-02210-3
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic kinase NEK2 regulates an RBFOX2-dependent pro-mesenchymal splicing program in triple-negative breast cancer cells

Abstract: Background Triple-negative breast cancer (TNBC) is the most heterogeneous and malignant subtype of breast cancer (BC). TNBC is defined by the absence of expression of estrogen, progesterone and HER2 receptors and lacks efficacious targeted therapies. NEK2 is an oncogenic kinase that is significantly upregulated in TNBC, thereby representing a promising therapeutic target. NEK2 localizes in the nucleus and promotes oncogenic splice variants in different cancer cells. Notably, alternative splicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 71 publications
2
33
0
Order By: Relevance
“…We recently found that NEK2 exerts widespread modulation of the alternative splicing program of MDA-MB-231 (GSE140803), a cell line representative of the TNBC subtype ( 25 ). A substantial fraction of the NEK2-regulated splicing events were dependent on the ability of the kinase to promote the expression of RBFOX2 ( 25 ), a splicing factor involved in the regulation of the epithelial-to-mesenchymal transition (EMT) process ( 25 ). However, other exons regulated by NEK2 lacked binding sites for RBFOX2 and were likely regulated by other splicing factors in TNBC cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently found that NEK2 exerts widespread modulation of the alternative splicing program of MDA-MB-231 (GSE140803), a cell line representative of the TNBC subtype ( 25 ). A substantial fraction of the NEK2-regulated splicing events were dependent on the ability of the kinase to promote the expression of RBFOX2 ( 25 ), a splicing factor involved in the regulation of the epithelial-to-mesenchymal transition (EMT) process ( 25 ). However, other exons regulated by NEK2 lacked binding sites for RBFOX2 and were likely regulated by other splicing factors in TNBC cells.…”
Section: Resultsmentioning
confidence: 99%
“…PolyA plus RNA-seq libraries were constructed according to Illumina’s protocol and sequenced using a 100-bp single-end format on an Illumina HiSeq 2000. RNA-Seq data analysis was performed by GenoSplice technology ( ), as previously described ( 25 , 35 ), using Human FAST DB v2016_1 annotations. Results were considered statistically significant for p -values ≤0.05 and fold-changes ≥1.5.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations